Business sustainability in the era of Fintech and Regtech: a systematic literature review - Sunaina Kanojia; Supreet Kaur; Bhavya (Discover Sustainability)
Abstract Purpose The present paper examines the existing literature on how FinTech and RegTech contribute to business sustainability and the sustainability of new-age technology firms. It highlights the opportunities and challenges faced by new age technology firms, especially in emerging markets, in ushering in business sustainability and provides insights to attain economic stability, growth, and social and environmental sustainability through FinTech and RegTech. Methodology We conducted a systematic literature review using the SALSA (Search, Appraisal, Synthesis, and Analysis) framework to examine existing literature on the topic of the current study. To analyse the evolution and development of this domain, we extract published literature from Scopus using search strings based on the PICOC (Population, Intervention, Comparison, Outcome and Context) framework population, without considering any time frame. Thematic synthesis is used for data extraction and further classification of literature to synthesize the current body of knowledge and ascertain future research agendas in FinTech, RegTech and sustainability. Finding We find that FinTech has favourable influence on banks, SMEs and agriculture performance but is a significant challenger to the traditional finance industry. Although, there is suggestive evidence in favour of cyber security being a factor for FinTech adoption, further evidence is still required. Results highlight differences in market penetration of FinTech in developed and emerging economies, and demographic factors like the age of the population and demographic dividend of the emerging economies play an important role in the rise of FinTech in emerging economies. RegTech has continuously evolved to address the challenges posed by evolving financial technologies, with a focus on improving internal control systems. This study outlines the future research agenda in terms of protection against non-compliance, money laundering, terror financing, and cyber security, which are other major reasons for the adoption of RegTech. RegTech has also shown a positive impact on preventing financial crime, reducing compliance costs, and easy onboarding of clients. Practical implications This paper reveals the connection between FinTech and RegTech and business sustainability, the factors that influence their adoption, and the challenges of adopting these technologies. The findings underscore the issues that policymakers must tackle to promote responsible FinTech adoption, striking a balance between innovation and sustainability. Originality To the best of the authors’ knowledge, this is the first study examining and presenting a structured literature review of the existing literature on the impact of FinTech/RegTech on business sustainability.